2019
DOI: 10.36740/wlek201903117
|View full text |Cite
|
Sign up to set email alerts
|

The State of Oxidative Homeostasis in Children With Influenza Stomatitis

Abstract: Introduction: The clinical course of acute respiratory viral infections was not sufficiently studied, specially the state of oxidative homeostasis in children with influenza stomatitis. This fact became the base for our study. The aim: to characterize the state of oxidative-prooxidant system as one of the factors of non-specific resistance of children` organism with influenza stomatitis. Materials and methods: A survey was conducted on 384 children with acute respiratory viral infections aged from 6 months to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In control mice, after 3 days of infection, the oxidase activity increased approximately twofold. The results are in good agreement with data that show, during influenza infection, the holo-Cp level in the blood increases together with other acute phase proteins and remains high throughout the infection [37,66]. This fact indicates that the increase in Cp gene expression occurs at the transcriptional level.…”
Section: Discussionsupporting
confidence: 91%
“…In control mice, after 3 days of infection, the oxidase activity increased approximately twofold. The results are in good agreement with data that show, during influenza infection, the holo-Cp level in the blood increases together with other acute phase proteins and remains high throughout the infection [37,66]. This fact indicates that the increase in Cp gene expression occurs at the transcriptional level.…”
Section: Discussionsupporting
confidence: 91%
“…Two studies found that during viral infection, serum hepcidin levels increased and iron levels decreased [ 169 , 170 ]. Blood plasma transferrin saturation by iron was significantly reduced in patients with severe forms of influenza stomatitis [ 171 ]. The mean hemoglobin level in infants and toddlers decreased with increasing numbers of infectious episodes [ 172 ].…”
Section: Resultsmentioning
confidence: 99%
“…In existing studies of viral infections and iron in children, decreased levels of serum hemoglobin, iron and plasma transferrin saturation were observed during infection [169][170][171][172]. The decrease in serum iron levels during infection may be due to increased hepcidin [311][312][313][314][315][316].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, the level of Cp in a patient’s blood serum rises several times and remains high during IAV infection [ 120 , 121 , 156 ]. This effect was viewed as a defensive response of the organism, and Cp was considered a potential nonspecific agent for prophylaxis and treatment of myxo- and paramyxovirus infections [ 118 ].…”
Section: The Points In Which Iav-induced Inflammation Cross With Copper Metabolismmentioning
confidence: 99%